Design of Game Attribute Development in Ikaan Studio Based on Consumer Preferences using Conjoint Analysis - Gregorius Sigit Hermawan Zavit; Sari Wulandari (Jurnal Rekayasa Sistem & Industri, 2021)
In updating or creating video games, developers must identify the preferences and attitudes of certain groupsof players towards the specifications and features available, ensuring the elements that make a game widelyplayed and get high ratings at the same time. Ikaan Studio is a developer company that develops the CitampiStories game, with problems with a lack of downloads and a rating that is not so high. The purpose of thisstudy is to develop game products at Ikaan Studio based on game attributes that match player preferences.This study uses conjoint analysis as a research method to find attributes that match the preferences of gameplayers. The first stage, begins with determining the important attributes and the level of game designattributes. Furthermore, the formation of a combination of stimuli using an orthogonal design. Finally, datafrom 209 samples were analyzed by conjoint analysis to determine player preferences. The results revealthat the "tutorial" attribute is the element that is considered the most important for players, followed by the"game mechanic" attribute with the same importance level. On the other hand, the attribute "object" isconsidered the least important. This study also shows that the preferences of players with different genderand age ranges which aims to provide insight to companies regarding preferences in the actual market.